Ethiopian Gender Strategy: Building equitable climate-resilient African bean and insect sectors - Miruts, Fitsum; Tsegaye, Dagmawit; Genanew, Tigist; Ketema, Dessalegn; Ouya, Frederick; Lutomia, Cosmas; Nchanji, Eileen (Bioversity International and International Center for Tropical Agriculture, 2025)
The Building Equitable Climate-Resilient African Bean and Insect Sectors (BRAINS) project is facilitating sustainable agricultural change throughout Sub-Saharan Africa, particularly in Ethiopia. The project seeks to enhance low-carbon, climate-resilient production systems and broaden inclusive livelihood options for rural communities. The initiative in Ethiopia targets the common bean, fruit trees, and insects for food and feed value chains, which possess significant potential to improve food and nutrition security, diversify revenue sources, and strengthen resilience among smallholder farmers amid escalating climate variability. The BRAINS project is fundamentally dedicated to gender equality and social inclusion, ensuring that women, men, and youth are actively involved, receive equitable benefits from interventions, and are enabled to engage in decision-making and value-chain governance.